2020
DOI: 10.14366/usg.19031
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utilization of shear wave dispersion imaging in diffuse liver disease

Abstract: Shear wave (SW) dispersion imaging is a newly developed imaging technology for assessing the dispersion slope of SWs, which is related to tissue viscosity in diffuse liver disease. Our preclinical and preliminary clinical studies have shown that SW speed is more useful than dispersion slope for predicting the degree of fibrosis and that dispersion slope is more useful than SW speed for predicting the degree of necroinflammation. Thus, dispersion slope, which reflects viscosity, may provide additional pathophys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
109
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(118 citation statements)
references
References 22 publications
(39 reference statements)
3
109
0
Order By: Relevance
“…But the common understanding is that viscosity in the human liver increases with higher fibrosis stages, as summarized in Table 6. Likewise, a recent study of Sugimoto et al [109] has tried to overcome the limitations of the former studies by enrolling subjects with a single etiology, and using the dispersion slope value instead of a simple Voigt model since there is no consensus in the clinical/elastography community with the most appropriate rheological model for soft tissue characterization. They put the focus of dispersion slope measurements on the lack of practical guidance.…”
Section: Livermentioning
confidence: 99%
“…But the common understanding is that viscosity in the human liver increases with higher fibrosis stages, as summarized in Table 6. Likewise, a recent study of Sugimoto et al [109] has tried to overcome the limitations of the former studies by enrolling subjects with a single etiology, and using the dispersion slope value instead of a simple Voigt model since there is no consensus in the clinical/elastography community with the most appropriate rheological model for soft tissue characterization. They put the focus of dispersion slope measurements on the lack of practical guidance.…”
Section: Livermentioning
confidence: 99%
“…(2) In general, liver fibrosis increases gradually in parallel with the stage progression of chronic liver disease. However, shear waves propagate disproportionally as fibrosis progresses [22,25,[41][42][43]. Namely, SWD is increased in hepatitis patients, whereas SWD is decreased in cirrhosis patients (with grade 4 or 5 severe fibrosis) [41,44].…”
Section: Discussionmentioning
confidence: 99%
“…Although SWE reflects both elasticity and viscosity (i.e., viscoelasticity) [22]. SWD is calculated based on SWD measurements and reflects viscosity only [24,25]. Since liver fibrosis advances gradually as hepatitis progresses [26], SWD may be able to estimate liver damage in an earlier stage than SWE.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, from shear wave speed and frequency, SWD can be estimated as a phase domain, and is calculated in units of (m/sec)/kHz [8,11]. Since 2D-SWI was introduced, several preliminary studies have reported the clinical significance of SWD in various hepatic diseases, both in a rat model and in human patients [8,11,21,22]. To our knowledge, this is the first study to evaluate secondary changes in the liver by 2D-SWI, focusing on the GB.…”
Section: Discussionmentioning
confidence: 99%